## non negative solution of the matrix equation $A^T U A = U - C$ if C is non-negative

Given $A$ a matrix with spectral radius smaller than 1 and a matrix $C$ symmetric. It can be shown that $U=\sum_{k=0}^\infty (A^T)^k C A^k$ converges, is symmetric and is the solution of the equation above.

Is it possible to show that if $C$ is non-negative also $U$ is non-negative?

-
In your infinite sum, all terms are nonnegative. Isn't this enough? – Federico Poloni Aug 21 at 10:23
Federico Poloni is absolutely right. – Bazin Aug 21 at 16:10
Cleary if all the terms are nonnegative I am done, but the matrix $A$ could have negative entries, then how can I be sure that each term is nonnegative? – Giovanni Aug 22 at 11:52
Wait, what do you mean by "nonnegative"? Entrywise or positive semidefinite? – Federico Poloni Aug 25 at 16:06
Entrywise. Now I doubt that the result holds, but I have not found a counter-examplet. I agree that if C is semidefinite positive, then U is semidefinite positive. – Giovanni Aug 28 at 8:57

Here is an alternative approach to solving the original equation.

The desired equation subject to the constraint $U \ge 0$ (elementwise nonnegativity) can be written as

\begin{equation*} U = C + A^TUA,\qquad U \ge 0. \end{equation*}

Define now the iteration:

\begin{equation*} U_{k+1} = [C + A^TU_kA]_+,\qquad k=0,1,\ldots \end{equation*} where $[\cdot]_+ \equiv \max\lbrace 0, \cdot\rbrace$ denotes projection onto the nonnegative orthant. Assuming the slightly stronger condition that the spectral norm $\|A\| < 1$, we can show that the above iteration converges to the desired solution.

$\newcommand{\Gc}{\mathcal{G}}$ Claim. Let $\Gc$ denote the map $U\mapsto [C + A^TUA]_+$. Then, $\Gc$ is a strict contraction in the spectral norm.

Proof. Let $U, V$ be two matrices. Then, \begin{eqnarray*} \|\Gc(U)-\Gc(V)\| &=& \|[C + A^TUA]_+ - [C + A^TVA]_+\|\\\\ &\le& \|C + A^TUA - C - A^TVA]\|\\\\ &\le& \|A^T(U-V)A\|\\\\ &\le& \|A^T\| \|A\| \|U-V\| \\\\ &\le& \gamma\|U-V\|,\qquad \text{where}\ \gamma=\|A\|^2 < 1. \end{eqnarray*} The first inequality follows as projection is a non-expansive operator, the rest follow from obvious properties of the spectral norm.

Thus, $\Gc$ is a strict contraction. So by the Banach contraction theorem the iteration $U_{k+1}=\Gc(U_k)$ has a unique solution. This solution is nonnegative by construction and satisfies the desired equation.

-